DEFENDING SCHOOL AGAINST CONTEMPORARY PEDAGOGIES - Aquino, Julio Groppa [UNESP] (Univ Estadual Campinas, Fac Educacao, 2017)
Being the book In defence of the school the common thread for the reflections herein, this article treads at first an argumentative path which encompasses be it the opposition to school practices, be it their apology, crossed by a brief digression around the critical work proposed by Michel Foucault, to which the arguments align from the theoretical standpoint. The specific aim of the article is a descriptive approach of some circulating utterances in the pedagogical-scholar contemporaneity, by means of analysing the filmic piece Quando sinto que ja sei, a 2014 Brazilian documentary comprised of testimonials by students, educators and visionaries of the so-called alternative schooling experiences. For the sake of adjuring certain pedagogical expedients deemed as anachronic, the film is centered in proposing allegedly innovative initiatives and strategies to teaching, to engaging its main actors and the latter to the school setting, pointing to a marked transfiguration of the typical normativity of pedagogical-scholar practices. As a counterpoint to the underlying rationality of the film and apprised of a certain vitalist skepticism, the article proposes, as its final remarks, an education by the archive, with regard to unlocking the institutive forces of the school ethos and, above all, of the teacher's word.
Keywords: Michel Foucault; School; Pedagogy; Documentary; Archive